'Environmental governance' and 'ecosystem management': avenues for synergies between two approaches. (2016) - Söderström, Sara; Kern, Kristine; Boström, Magnus; Gilek, Michael
Based on a literature review of over 160 journal articles and books, this article examines the ecosystem management and environmental governance approaches, and looks for common topics and integrated research agendas. While scientific articles on environmental governance stem primarily from social science research, the ecosystem management approach is more natural science-oriented. A review of journal articles from the ISI Web of Knowledge (Web of Science) reveals that the two research communities hardly interact. The paper discusses two thematic linkages between the two approaches: the debates dealing with the scale and level of environmental policy; and the discussions surrounding multi-stakeholder participation. Moreover, the article identifies areas with a high potential for the establishment of common ground, such as the current discussion on science-policy interfaces. We argue for more interaction, claim that the two research approaches can learn from each other, and discuss the potential for the development of interdisciplinary research agendas.